Improving organisational performance – red team policing and partnerships. Issue 2 (2014) - Geoff Coliandris; Colin Rogers
<x xml:space="preserve"> Abstract </x> Purpose – Intra and inter‐organisational learning holds important consequences for official agencies' capabilities to reduce harm, particularly in the field of safeguarding children. A range of formal learning mechanisms exist but as these can be limited there is a case for expanding the learning opportunities relied upon. The concepts of "red teaming" and "alternative analysis" though relatively well established in other sectors are under‐developed, under‐used and under‐promoted within policing. They offer flexible conceptual and practical resources that aim to challenge established models, thinking and practices. Policing organisations would benefit from institutionalising alternative forms of analysis though this would involve an attitudinal commitment and shift. This paper aims to discuss these issues. Design/methodology/approach – Documentary analysis and reflection. Findings – Consideration of the red team approach by police and partners offers an alternative approach to effective organisational learning to prevent repeating similar mistakes uncovered by Serious Case Reviews. Originality/value – This paper will allow practitioners to reflect upon current serious reviews of cases and offers an alternative and effective way of improving partner agencies capabilities to reduce harm.